2007
DOI: 10.1590/s0100-83582007000200023
|View full text |Cite
|
Sign up to set email alerts
|

Influência de sais e do pH da água na eficiência de imazethapyr + imazapic no controle de arroz-vermelho

Abstract: RESUMO -Na safra agrícola de 2004/2005, em Santa Maria/RS, foi realizado um experimento com o objetivo de avalia r a influência de sais e do pH da água de diferentes fontes de abastecimento de pulverizadores (água de fonte mineral, água de açude e água de poço artesiano) sobre a eficiência de imazethapyr (75 g L ) no controle de arroz-vermelho (Oryza sativa). No preparo da calda para pulverização do herbicida, foi utilizada água na sua condição original e água acidificada com ácido cítrico até pH 4,5. Foi veri… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
1
0
3

Year Published

2007
2007
2020
2020

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(4 citation statements)
references
References 2 publications
(2 reference statements)
0
1
0
3
Order By: Relevance
“…The best results were obtained in the period up to 42 DAA with Iharaguen™ and Orobor N1™, and the highest dose of the in-tank mixture of bispyribac-sodium + metsulfuron-methyl (40 + 3.3 g ai ha -1 ), associated with the adjuvants LI 700™ and TA 35™, presented better performance, compared to the lowest studied dose. Sanchotene et al (2007) found that water from the spray solution acidified at pH 4.5 enhanced the effectiveness of the ALS-inhibiting herbicides imazethapyr + imazapic on red rice control (Oryza sativa). However, this response was not observed in the control of globe fringerush using the herbicides bispyribac-sodium + metsulfuron-methyl since the adjuvant LI 700™, although it has promoted the highest pH reduction in the solutions, did not stood out regarding efficiency.…”
Section: Resultsmentioning
confidence: 99%
“…The best results were obtained in the period up to 42 DAA with Iharaguen™ and Orobor N1™, and the highest dose of the in-tank mixture of bispyribac-sodium + metsulfuron-methyl (40 + 3.3 g ai ha -1 ), associated with the adjuvants LI 700™ and TA 35™, presented better performance, compared to the lowest studied dose. Sanchotene et al (2007) found that water from the spray solution acidified at pH 4.5 enhanced the effectiveness of the ALS-inhibiting herbicides imazethapyr + imazapic on red rice control (Oryza sativa). However, this response was not observed in the control of globe fringerush using the herbicides bispyribac-sodium + metsulfuron-methyl since the adjuvant LI 700™, although it has promoted the highest pH reduction in the solutions, did not stood out regarding efficiency.…”
Section: Resultsmentioning
confidence: 99%
“…As transformações utilizadas foram √ + 1 para as variáveis número de percevejos por metro antes, e com 24 e 72 horas após a aplicação.A eficiência de controle foi transformada utilizando o arco-seno √%/100 +0,5. & MOSCARDI, 2002;HIRATA ET al., 2003;OLIVEIRA ET al., 2005;SANCHOTENE ET al., 2007;AZEVEDO, 2011).…”
Section: Amostragens E Análises Estatísticasunclassified
“…A dureza da água em pulverização é outro fator que interfere no desempenho dos pesticidas (Buhler & Burnside, 1983;Sanchotene et al, 2007). Para a correção, pode ser inserido um agente complexante de metais à calda de pulverização, antes da adição do herbicida, visando à eliminação da reatividade dos íons presentes em solução.…”
Section: Introductionunclassified